A case of synchronous bilateral calyx urothelial carcinoma: combined treatment approach - Semko, S.; Pikul, M.; Voylenko, O.; Stakhovskyi, O.; Kononenko, O.; Vitruk, Yu.; Stakhovsky, E. (PH Akademperiodyka, 2023)
Summary. Upper urinary tract urothelial carcinoma is a rare tumor. Data about its correct management are controversial. Investigational technology development made it possible to diagnose asymptomatic small tumors, which can be successfully managed endoscopically. We report the case of bilateral urothelial cancer and hydronephrosis in patient aged 38. After management of acute post-renal kidney insufficiency, the neoadjuvant platinum-based chemotherapy was used followed by the kidney-sparing surgery split in two interventions on both sides. The patient does not have any relapse or further progression after one year of initial treatment with good performance status and high life quality level. We believe that the kidney preserving strategy can be considered as an option even in high-risk patients. The renal function in such cases is a crucial parameter affecting the outcome.